Pengaruh Work-Life Balance Serta Turnover Intention Terhadap Kesejahteraan Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Puskesmas Rimbo Ilir - Mutiyah Khansa; Yulasmi; Bayu Pratma Azka (CV. ITTC INDONESIA, 2025)
The aim of this research is to find out how much influence Work Life Balance and Trunover Intention have on Employee Welfare through Job Satisfaction among Rimbo Ilir Jambi Health Center Employees. The sample used was a saturated sample, because the entire population was sampled, namely 42 respondents. Data collection techniques through questionnaires that have been tested for validity and reliability, Partial Least Square (PLS) are used to test the hypothesis in this research using SmartPLS 4.0. The results of this research show that work life balance has a positive and insignificant effect on job satisfaction. and Trunover Intention has a positive and significant influence on job satisfaction, work life balance has a positive and not significant influence on employee well-being, Trunover intention has a positive and significant influence on employee welfare, and job satisfaction has a positive and not significant influence on employee welfare. Work Life Balance has a positive and insignificant effect on employee welfare through job satisfaction. Trunover Intention has a positive and insignificant effect on employee welfare through job satisfaction.